Towards Self-Aware Approach for Mobile Devices Security - Nanda Kumar Thanigaivelan; Ethiopia Nigussie; Seppo Virtanen; Jouni Isoaho (My University, 2022)
We present conceptual design of self-aware security for mobile devices. The design is envisioned to bring self-awareness into the mobile devices security for optimal protection by regulating application activities. The proposed design contains three subsystems: meta-level enables self-awareness, extended meta-level extends protections to the base-level components through security mechanisms and base-level comprises of resources that are essential for applications execution. The presented design enables cooperation among security mechanisms (such as access control and anti-virus) as well as with self-aware agent. The cooperation is intended for better understanding of application activities that leads to recognizing threat patterns in advance. When a threat is predicted/detected, the self-aware agent communicates with the security mechanisms so that they can take the necessary actions. The design of the security mechanisms are elaborated using access control system and anti-virus as example cases.
Computer Network Security